2020
DOI: 10.2478/ethemes-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Income Tax on Gross Domestic Product - The Case of the Republic of Serbia

Abstract: The importance of certain tax forms for the economy of any country is confirmed by the fact that they can be used to impact on the achievement of fiscal aims as they play a significant role when it comes to their share in a total amount of public revenue of certain countries. Another important characteristic of taxes is that they can affect the trends of gross domestic product (GDP) as one of the most important economic indicators of achieved development of a national economy. It is for this reason that we mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The fiscal impact of CIT on economic expansion is the primary focus in many books that delve into business tax. Đurović Todorović et al (2020) scrutinized the influence of Serbia's CIT on the country's economic growth. They concluded that an increase in CIT positively affects the economy's growth (Đurović Todorović et al, 2020, p. 321).…”
Section: The Literature On Corporate Tax Revenuesmentioning
confidence: 99%
“…The fiscal impact of CIT on economic expansion is the primary focus in many books that delve into business tax. Đurović Todorović et al (2020) scrutinized the influence of Serbia's CIT on the country's economic growth. They concluded that an increase in CIT positively affects the economy's growth (Đurović Todorović et al, 2020, p. 321).…”
Section: The Literature On Corporate Tax Revenuesmentioning
confidence: 99%